2013
DOI: 10.1093/ejcts/ezt003
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in right vs left ventricular recovery during follow-up after ventricular septal defect correction in children

Abstract: Within the first year after VSD correction, LV systolic performance had normalized, while RV systolic performance remained significantly impaired up to 20 months after VSD closure. Both detrimental effects of open heart surgery with cardiopulmonary bypass and preoperative alterations may add to the observed postoperative impairment of specifically RV performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…50-62,64-69 There were eight manuscripts eligible from Friedberg and Mertens et al (Toronto) 20,50-56 and six manuscripts eligible from Marcus et al (Netherlands) 16,58-62 that compared strain from a large database of overlapping pediatric controls to different disease outcomes in children, or healthy children. In consultation with the authors, the datasets from Fernandes et al 20 (Toronto) and Marcus et al 16 (Netherlands) were chosen as they contained the largest amount of control patients.…”
Section: Electronic Database Search Hedgesmentioning
confidence: 99%
“…50-62,64-69 There were eight manuscripts eligible from Friedberg and Mertens et al (Toronto) 20,50-56 and six manuscripts eligible from Marcus et al (Netherlands) 16,58-62 that compared strain from a large database of overlapping pediatric controls to different disease outcomes in children, or healthy children. In consultation with the authors, the datasets from Fernandes et al 20 (Toronto) and Marcus et al 16 (Netherlands) were chosen as they contained the largest amount of control patients.…”
Section: Electronic Database Search Hedgesmentioning
confidence: 99%
“…The mechanisms of impaired ventricular function and mechanics in patients after repair of different types of VSDs are not entirely clear. Klitsie et al have shown that the right ventricle is more vulnerable than the left to the effects of cardiopulmonary bypass after repair of various types of VSDs . Hypothesized mechanisms include greater susceptibility of the thin‐walled right ventricle to inflammatory cascades of cardiopulmonary bypass, greater risk of external warming of the anteriorly located right ventricle during bypass, influence of pericardiotomy and pericardial adhesions and pressure overload .…”
Section: Discussionmentioning
confidence: 99%
“…Klitsie et al have shown that the right ventricle is more vulnerable than the left to the effects of cardiopulmonary bypass after repair of various types of VSDs. 27 Hypothesized mechanisms include greater susceptibility of the thin-walled right ventricle to inflammatory cascades of cardiopulmonary bypass, 28,29 greater risk of external warming of the anteriorly located right ventricle during bypass, 30 influence of pericardiotomy and pericardial adhesions and pressure overload. 31 Our findings of significant associations between RV and LV deformation parameters further suggest that ventricular interdependence may explain in part the LV involvements.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term follow-up studies to assess cardiac function after correction of congenital heart defects are as yet lacking. However, a recent study by Klitsie et al 3 4 that preoperative values were similar to normal (6.2 AE 1.3 cm/sec). It might be that anesthesia has already a negative influence on LV function preoperatively, since the patients of Pauliks et al were studied in the operating room, in contrast to the 1 day preoperative investigation by Klitsie et al [2][3][4] These differential findings further underscore the use of normal controls in interpreting results.…”
mentioning
confidence: 87%